2012
DOI: 10.3390/nu4091317
|View full text |Cite
|
Sign up to set email alerts
|

Poor Knowledge and Practices Related to Iodine Nutrition during Pregnancy and Lactation in Australian Women: Pre- and Post-Iodine Fortification

Abstract: A before-after review was undertaken to assess whether knowledge and practices related to iodine nutrition, supplementation and fortification has improved in Australian women since the introduction of mandatory iodine fortification in 2009. Surveys of pregnant (n = 139) and non-pregnant (n = 75) women in 2007–2008 are compared with surveys of pregnant (n = 147) and lactating women (n = 60) one to two years post-fortification in a regional area of New South Wales, Australia. A self-administered questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 20 publications
4
68
4
2
Order By: Relevance
“…The present study helps to understand what type of public actions need to be implemented to raise public awareness or maintain it at a sufficient level. Assessment of knowledge about iodine is conducted mostly in regions were iodine deficiency is more severe (Jooste et al, 2005;Girma et al, 2012;Khan et al, 2012) or for vulnerable groups like pregnant women (Charlton et al, 2012;O'Kane et al, 2015). The main findings of the studies were that even for vulnerable groups the level of awareness was low and that the level of awareness increased with the level of education and socio-economic situation of respondents.…”
Section: Discussionmentioning
confidence: 87%
“…The present study helps to understand what type of public actions need to be implemented to raise public awareness or maintain it at a sufficient level. Assessment of knowledge about iodine is conducted mostly in regions were iodine deficiency is more severe (Jooste et al, 2005;Girma et al, 2012;Khan et al, 2012) or for vulnerable groups like pregnant women (Charlton et al, 2012;O'Kane et al, 2015). The main findings of the studies were that even for vulnerable groups the level of awareness was low and that the level of awareness increased with the level of education and socio-economic situation of respondents.…”
Section: Discussionmentioning
confidence: 87%
“…16 The result of our study show that more than half of respondent (56%) have knowledge about iodine deficiency disorder. Niksic et al reported that only half of the participants (49.1%) know of iodine deficiency disorder.…”
mentioning
confidence: 70%
“…Charlton, et al in study conducted in Australian women reported that knowledge of dietary sources of iodine was also found to be poor. 16 Jooste, et al showed that, only 15.4% of respondents correctly identified iodized salt as the primary dietary source of iodine. 4 Sebotsa et al showed that knowledge on the main source of iodine in food consumed by the people in South Africa, a higher percentage of patients (76.7%) lacked knowledge of iodine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among pregnant women in 2011-2012, 60%-66% were taking supplements containing iodine [43]. This means that up to 40% of women were still not taking recommended iodine supplements, which the authors suggested might be due to women not being informed about the need for supplementation by their antenatal care providers, despite there being written advice on supplements provided in public health facilities across NSW.…”
Section: Mackerras Et Al Evaluated Iodine Status In Aboriginal Austrmentioning
confidence: 91%